Evaluation of the National Archives Website in Terms of Its Use by Researchers Before Field Visits - Cengiz Mater, Emine (Information World, 2025)
In recent years, the integration of digital technologies into the field of archival science has brought significant changes to information access processes. Researchers now have the opportunity to prepare for their visits by using online resources before physically going to the archives. This situation makes it essential for archival websites to play a key role in access to information and research planning. This study aims to evaluate the functionality of the website of the Republic of Türkiye State Archives, in order to support researchers in their online preparation before visiting the archives in person. In the research, the ARPO (Archival Research Preparation Online) Index Evaluation Tool was used to measure the contribution of archival websites to pre-visit research preparation processes. Based on a descriptive research design and qualitative content analysis, the study assessed various features of the National Archives website, including information access tools, material request processes, and user support services. According to the findings, while the website has user-friendly features in some areas (such as information collection and search boxes), it lacks functionality in critical services like online communication, material requests, and appointment scheduling. As a result of the study, the total ARPO score of the website was calculated as 52 out of 90. The findings of the study reveal that several aspects of the National Archives website’s online services need to be improved in order to enhance the user experience. It is hoped that this research will contribute to the literature on digital archival services and provide a basis for future studies.